Design thinking, fast and slow: A framework for Kahneman's dual-system theory in design. (2019) - Kannengiesser, Udo; Gero, John S.
Abstract : In his book Thinking, Fast and Slow, Daniel Kahneman presented a model of human cognition based on two modes or 'systems' of thinking: system 1 thinking that is fast and intuitive and system 2 thinking that is slow and tedious. This paper proposes a framework for applying Kahneman's model to designing based on the function–behaviour–structure ontology. It casts four instances of designing in this framework: design fixation, case-based design, pattern-language-based design and brainstorming.